Cardiac troponin C (TnC) and a site I skeletal TnC mutant alter Ca(2+)versus crossbridge contribution to force in rabbit skeletal fibres - Moreno-Gonzalez, Alicia (Blackwell Science Inc, 2005)
We studied the relative contributions of Ca(2+) binding to troponin C (TnC) and myosin binding to actin in activating thin filaments of rabbit psoas fibres. The ability of Ca(2+) to activate thin filaments was reduced by replacing native TnC with cardiac TnC (cTnC) or a site I-inactive skeletal TnC mutant (xsTnC). Acto-myosin (crossbridge) interaction was either inhibited using N-benzyl-p-toluene sulphonamide (BTS) or enhanced by lowering [ATP] from 5.0 to 0.5 mm. Reconstitution with cTnC reduced maximal force (F(max)) by ∼1/3 and the Ca(2+) sensitivity of force (pCa(50)) by 0.17 unit (P < 0.001), while reconstitution with xsTnC reduced F(max) by ∼2/3 and pCa(50) by 0.19 unit (P < 0.001). In both cases the apparent cooperativity of activation (n(H)) was greatly decreased. In control fibres 3 μm BTS inhibited force to 57% of F(max) while in fibres reconstituted with cTnC or xsTnC, reconstituted maximal force (rF(max)) was inhibited to 8.8% and 14.3%, respectively. Under control conditions 3 μm BTS significantly decreased the pCa(50), but this effect was considerably reduced in cTnC reconstituted fibres, and eliminated in xsTnC reconstituted fibres. In contrast, when crossbridge cycle kinetics were slowed by lowering [ATP] from 5 to 0.5 mm in xsTnC reconstituted fibres, pCa(50) and n(H) were increased towards control values. Combined, our results demonstrate that when the ability of Ca(2+) binding to activate thin filaments is compromised, the relative contribution of strong crossbridges to maintain thin filament activation is increased. Furthermore, the data suggest that at low levels of Ca(2+), the level of thin filament activation is determined primarily by the direct effects of Ca(2+) on tropomyosin mobility, while at higher levels of Ca(2+) the final level of thin filament activation is primarily determined by strong cycling crossbridges.